Study of the Quality of Public Services in Public Catering Companies: Methodology, Analysis and Assessment - Isaenko, Anatoly Vladimirovich; Korolev, Aleksey Vasilievich (International Review of Management and Marketing, 2016)
The article substantiates the urgency, importance and necessity of developing a set of theoretical provisions and practical recommendations on the improvement of the quality of public services provided in public catering companies. The authors suggest their own interpretation of the process of services provision in public catering companies. We have studied the genesis of Russian public catering services market, provided the periodization of the historic stages of its emergence and development distinguishing the key factors, which influence the quality of services provision to customers. The article studies the evolution of methodical approaches to the definition of services quality to customers and the ways of its measuring. According to the obtained results the article defines advantages and disadvantages of the main methodical approaches; provides argumentation for the necessity of adding the methods of services quality assessment with the methods of marketing analysis (PEST and SWOT), which enable to take into consideration the influence of external and internal factors on the quality of public services at public catering companies. The article provides the SWOT matrix of public catering companies’ activity on improving the quality of public services; it also gives the algorithm and approbation of the authors’ procedure of the services quality assessment at public catering companies, based on the paradigm “confirmation/non-confirmation of expectations”, and develops recommendations on its realization. The practical importance of the study is in the fact that the developed methodical and managerial set of tools creates the basis for the development of the efficient system of quality public services at public catering companies and it can be applied by the organizations of different forms of ownership with the view of assessing the quality of services, substantiating and realizing conceptual directions of its improvement. Keywords: public catering, quality of public services, assessment algorithm JEL Classification: L3